Analisis Ekonomi Politik Korupsi di Perusahaan Listrik Negara (Sebuah Tinjauan dari Perspektif Teori Kleptokratik terhadap Kasus Listrik Swasta PLTU Paiton I) - Ulul Albab (Jurnal Aplikasi Manajemen, 2010)
In Indonesia, corruption has been so endemic inside the country that it affects everyone from the village level to the center of power in Jakarta. Massive corruption has been blamed as one of the causes of Indonesia's economic stagnation that occurred after the Asian Economic Crisis. Why corruption is so prevalent and what factors make corruption so prevalent in Indonesia?. This letter try to explain the causes of endemic corruption in Indonesia with three theories: mainstream economic theory, patrimonialism, and kleptocratic state theory. This tulisan also try to discussion about the distinguish between "mainstream" and "kleptocratic" that very interesting. The mainstream economic theory see that in the state that government policies intervene in the economy would result in rentseeking behavior, but in the state that more open competitive economies would have less corruption. The kleptocratic state theory see that even policies to reduce economic activities of the state and making it more competitive and open could also result in rentseeking behavior, if government officials see an opportunity to enrich themselves during the process and have an ability or power to manipulate the outcome of the transaction. The case of corruption in PLN is case of political economic of corruption that can to be explained on that three theories.